2018
DOI: 10.1088/1752-7163/aaba84
|View full text |Cite
|
Sign up to set email alerts
|

Nonhuman primate breath volatile organic compounds associate with developmental programming and cardio-metabolic status

Abstract: Rodent and nonhuman primate studies indicate that developmental programming by reduced perinatal nutrition negatively impacts life course cardio-metabolic health. We have developed a baboon model in which we feed control mothers (CON) ad libitum while nutrient restricted mothers are fed 70% of ad libitum global feed in pregnancy and lactation. Offspring of nutrient restricted mothers are intrauterine growth restricted (IUGR) at term. By 3.5 years IUGR baboons showed signs of insulin resistance, indicating a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…We have developed a well-established nonhuman IUGR primate model to evaluate the effects of moderate maternal nutrient reduction (MNR) in which baboon mothers were fed 70% of the global diet eaten by controls fed ad libitum during pregnancy and lactation (10)(11)(12)(13)(14)(15). At birth, MNR offspring were IUGR weighing ~89% of control offspring (16).…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a well-established nonhuman IUGR primate model to evaluate the effects of moderate maternal nutrient reduction (MNR) in which baboon mothers were fed 70% of the global diet eaten by controls fed ad libitum during pregnancy and lactation (10)(11)(12)(13)(14)(15). At birth, MNR offspring were IUGR weighing ~89% of control offspring (16).…”
Section: Introductionmentioning
confidence: 99%
“…By implementing a machine learning model to assess the normalized data, a predictive model based on the selected features could be built to inform diagnostic potential of exhaled breath signatures. Our previous studies in nonhuman primates identified exhaled breath signatures in animals with IR 19 . The adoption of the HOMA-IR categories was based on a population-based study reported from the adult Mexican Americans population 21 , as no clear definition exist for the Hispanic adolescents with IR.…”
Section: Non-invasive Exhaled Breath As Ir Diagnosismentioning
confidence: 98%
“…Although the other six breath metabolites did not reach significance between the groups individually (Supplementary Figure S5), their contribution to the breath-IR model is evident when assessing the diagnostic capability of the model (Figure 5) to identify individuals with IR. A combined signature of breath metabolites is clearly more informative than using a single metabolite which may be indicative of some normal variability in metabolites within and between individuals 15,19,42 .…”
Section: Non-invasive Exhaled Breath As Ir Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Non-human primate (NHP) models, such as baboons, have been used extensively to study cardiometabolic disorders in response to Western and other diets [14][15][16][17]. These studies benefit from the similarity in metabolism and nutritional needs of these animals compared to humans, and a controlled environment in which diets of defined composition can be fed without having to account for variable prior exposures of animals.…”
Section: Introductionmentioning
confidence: 99%